Comparison of Enteral versus Intravenous Potassium Supplementation in hypokalaemia in postcardiac surgery paediatric cardiac intensive care patients: prospective open label randomised control trial (EIPS). Issue 9 (4th September 2014) - Merchant, Quratulain; Rehman Siddiqui, Naveed ur; Rehmat, Amina; Amanullah, Muneer; Haq, Anwar ul; Hasan, Babar
Abstract : Background: Hypokalaemia is frequently encountered in the daily clinical practices of a paediatric cardiac intensive care unit (PCICU). It is a strong independent predictor of mortality in patients with heart failure. Thus, prompt potassium replacement therapy holds pivotal importance in therapy for hypokalaemia. Although intravenous potassium replacement (IVPR) in hypokalaemia is the preferred route in most intensive care settings, it is associated with known safety risks and can lead to arrhythmias, cardiac arrest and death if inappropriately administered. Enteral potassium replacement (EPR), with its superior safety profile, may be a better alternative to IVPR. Outcome: Primary outcome To compare the efficacy EPR and IVPR for treatment of hypokalaemia. Secondary outcome measures include a comparison of adverse effects (hyperkalaemia, diarrhoea, gastrointestinal bleeds, nausea and vomiting) after EPR and IVPR and a comparison of the number of dose/s required to achieve resolution of hypokalaemia for each episode of hypokalaemia. Methods and analysis: The Enteral Versus Intravenous Potassium Supplementation trial is designed as a randomised, controlled, non-blinded trial with two arms. Intervention arms will be block randomised on alternate weeks for IVPR and EPR. Recruited patients will receive treatment accordingly. For analysis, the percentage change in serum potassium levels in mEq/L after each event of potassium replacement in both arms will be used as an end point to compare the efficacy EPR and IVPR for treatment of hypokalaemia. Study setting: The study will be conducted at the PCICU at the Aga Khan University Hospital, Karachi. Ethics and dissemination: This study has been approved by the Ethics Review Committee and Clinical Trials Unit at The Aga Khan University with respect to scientific content and compliance with applicable research and human subjects regulations. Trial registration number: This trial is registered at Clinical Trials.Gov. Registration number: NCT02015962 .